(untitled) (Nexo Revista Científica, 2023)
Present study core aim was to investigate the impact of health care administration ultimately on patient behavior. Study was conducted in Riyadh Saudi Arabia. Study was conducted in Riyadh private health clinics. Total 4 (Four) constructs were considered and four hypotheses were developed. Based on the study framework, the research questions were developed and answered through the study findings. Total of 320 surveys questionnaire were distributed among the visitors or the attendants with the patients. However, valid responses were counted as 281. Data set then prepared while using SPSS version 23. All the necessary tests were conducted, such as Cronbach alpha, standard deviation, mean value calculation, hypotheses testing etc. Links between the hypotheses shows the positive association with the assumed relationship.